A poesia de dom Pedro Casaldáliga: doadora de sentido libertador - Migotto, Clóvis José (2017)
This dissertation aims to investigate the poetry of Pedro Casaldáliga, approaches in a cut of his poetic production and seeks to perceive a specific meaning. Inserted in the context of his Prelature of São Felix do Araguaia Pedro Casaldáliga matured his expression as a poet in the measure of his commitment to the liberation of his people. Every trace of his human and poetic thought, therefore, can be understood by the search for meaning to be a Christian witness of the proposal of the Kingdom of God. His poetry is integrated into the theoretical universe known as Liberation Theology and pervades the various experiences lived by the poet Casaldáliga in the region of Araguaia, Central America and Europe. The meaning of his poetry will be researched from his development as a poet, starting from his first verses until gaining emphasis his prophetic poetry. In a reflection on the historical retrospection of the process of colonization of the American Continent and, specifically, of Brazil, we take into account the colonizing function of the Christian faith that arrived here with the caravels of the Spanish and Portuguese conquerors, but also, Same faith, in defense of the conquered peoples. It follows that there is a knowledge on the part of the oppressed that seeks to resist the oppressor ever since. Understanding the poetry of Pedro Casaldáliga as knowledge that resists and liberates the colonized oppressed proves to be of fundamental importance for the analysis of the search for meaning of poetry in contexts of life marked by relations of oppression, resistance and hope of liberation